The Notary's Position in Making Credit Agreements for the Provision of Credit Facilities by Banks (Study of Batam Court Decision Number 36/Pdt. G/2021/PN Btm) - Immi Ira Monalisa Saragih; Dave Jehuda Hutama; Edrick Manuel Gunadi; Radot Marulitua Sihaloho; Surya Wardhana; Yudis Fajar Damanik (International Journal of Integrative Sciences, 2023)
In the midst of globalization and rapid economic growth. In an increasingly competitive business environment, business actors must continue to strengthen capital and business financing, and one method commonly used is through credit loans from financial institutions, such as banks. The role of banks and financial institutions as providers of capital has important implications in supporting economic growth and corporate activity. They act as intermediaries between public funds and borrowers, and participate in the implementation of national development, which involves economic equality, economic growth and national stability. In the legal context, credit agreements have a very important meaning   in   regulating   the   relationship   between creditors (banks) and debtors (borrowers). The role of the Notary  as  a  public  official  in  drafting  credit agreement deeds   is   to ensure   that the agreement complies with legal  provisions,  applies  fairly  to  all parties involved,  However,  the  problems  in  credit agreements arise Batam District Court Decision Case Number 36/Pdt.G/2021/PN Btm discusses a situation where credit guarantees in the form of land certificates face serious  obstacles.  The  cause  was  an  internal blockade carried out by the National Land Agency, which resulted in the Notary being unable to bind the guarantee with a mortgage right. Through this case study, this article provides valuable insight into legal issues that may arise in banking credit practices in Indonesia